Sick leave patterns as predictors of disability pension or long-term sick leave: a 6.75-year follow-up study in municipal eldercare workers. Issue 2 (7th February 2014) - Stapelfeldt, Christina Malmose; Nielsen, Claus Vinther; Andersen, Niels Trolle; Krane, Line; Borg, Vilhelm; Fleten, Nils; Jensen, Chris
Abstract : Objectives: The aim was to study whether a workplace-registered frequent short-term sick leave spell pattern was an early indicator of future disability pension or future long-term sick leave among municipal eldercare workers. Setting: The municipal healthcare sector in the city of Aarhus, which is the second largest city in Denmark. Participants: All elder care employees who worked the entire year of 2004 in the municipality of Aarhus, Denmark (N=2774). The employees' sick leave days during 2004 were categorised into: 0–2 and 3–17 short (1–7 days) spells, 2–13 mixed short and long (8+ days) spells and long spells only. Student workers (n=180), employees who were absent due to maternal/paternal leave (n=536) and employees who did not work the entire year of 2004 (n=1218) were not included. Primary outcome: Disability pension and long-term sick leave (≥8 weeks) were subsequently identified in a National register. The cumulative incidence proportion as a function of follow-up weeks was estimated using the Kaplan-Meier curve. The relative cumulative incidence (RR) of experiencing events within 352 weeks was analysed in a generalised linear regression model using the pseudo values method adjusted for age, occupation, unfavourable work factors and sick leave length. Results: A frequent short-term and a mixed sick leave pattern showed RRs of being granted a disability pension of 2.08 (95% CI 1.00 to 4.35) and 2.61 (95% CI 1.33 to 5.12) compared with 0–2 short spells. The risk of long-term sick leave was significantly increased for all sick leave patterns compared with 0–2 short spells. Adding sick leave length to the models attenuated all RRs and they became non-significant. Conclusions: Sick leave length was a better indicator of future workability than spell frequency. Preventive actions should target employees engaged in homecare. The more sick leave days the greater the preventive potential seems, irrespective of spell frequency.